GRHL2 Expression Functions in Breast Cancer Aggressiveness and Could Serve as Prognostic and Diagnostic Biomarker for Breast Cancer. (July 2022) - Bai, Xiaoyu; Li, Yue; Li, Yanlei; Li, Fan; Che, Na; Ni, Chunsheng; Zhao, Nan; Zhao, Xiulan; Liu, Tieju
Background: Breast cancer (BC) is the most frequent malignancy in women worldwide and the leading cause of female cancer–associated death in the world. Grainyhead-like 2 ( GRHL2 ) is an important gene involved in human cancer progression. However, the role of GRHL2 in BC is unknown. Methods: In this study, we used in vitro experiments to verify the role of GRHL2 expression in BC progression. We used 14 databases to analyse the expression level of GRHL2 in BC and its prognostic and diagnostic value. In addition, the correlation between GRHL2 expression and immune cell infiltration and DNA methylation was also analysed. Results: At the cellular level, overexpression of GRHL2 induced E-cadherin expression in BC cells with a mesenchymal phenotype and resulted in a hybrid epithelial/mesenchymal (E/M) phenotype, which is more strongly correlated with tumour aggressiveness than a pure mesenchymal phenotype. Through analysis of various databases, we found that tumour tissue had a higher expression level of GRHL2 . High expression of GRHL2 was associated with worse prognosis of BC patients and indicated that GRHL2 had significant diagnostic value. Grainyhead-like 2 is also related to immune infiltration and regulated by DNA methylation. Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) analyses showed that GRHL2 -related signalling pathways in BC were related to tumour cell proliferation, invasion, and angiogenesis. Conclusions: In summary, evidence indicates that GRHL2 can be used as a prognostic and diagnostic biomarker for BC.